Community tourism and new attractions in the Calchaquíes Valleys, Salta: the case of the Rural Tourism Network (Huellas, 2015)
In recent years theprovinceofSaltahas strengthened its presence in the Argentine tourist map. This involved, among other things, the increase of tourist offers to enjoy theprovinceofSalta. In this paper, we aim to address tourist diversity inSalta, especially observing how theCalchaquíesValleys, a traditional destination in the Argentine northwest, is redefined through new attractions and tourist services based on some local distinctive features. This work specifically approaches the way in which the tourist proposal in this area is renewed considering the creation of a rural and touristic organization- the Rural Tourism Network- that offers tourist services under the form of community-based tourism. It also aims at focusing attention on the social and territorial changes that the presence of this new actor, central to the diversification of tourist options in this destination, has introduced into the local scene.
Keywords: Community-based tourism; Rural Tourism Network; Calchaquíes Valleys; Salta; Argentina